Concept of future sports managers’ professional competences formation - Kryshtanovych, Myroslav; Kryshtanovych, Svitlana; Havrylyuk, Marianna (Lviv Politechnic Publishing House, 2017)
The article is devoted to the problem of the concept of future sports managers' professional competences formation. The authors defined that the concept of future sports managers' professional competences formation should be based on three main approaches: methodological, theoretical and practical ones. They state, that the higher educational institutions have to apply innovative teaching methods, improve holistic professional objectives/targets, and form professional skills, which will lead to the competitiveness of labour market. It has been proved that the content of practical readiness of future managers of physical culture and sports should be demonstrated in external (subject) skills, namely in actions that can be observed. These include organizational, mobilization, communicative and perceptual skills.
Keywords: concept; competence; sports manager; physical training; sport; scientific approach; methodology; pedagogical technologies